2012
DOI: 10.1188/12.onf.e353-e360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Art Making on Cancer-Related Symptoms of Blood and Marrow Transplantation Recipients

Abstract: Individuals receiving BMT may benefit from participation in art-making interventions. Art making is easy to implement in a clinic setting and allows for positive interactions between nurses and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 44 publications
0
29
1
5
Order By: Relevance
“…Previous studies have demonstrated some change in cortisol levels as a result of an art task (Lawson et al, 2012;Walsh et al, 2007). To the best of our knowledge, this is the first study to demonstrate reductions in cortisol levels in healthy adults as a result of art making in a format structured to be similar to an art therapy session.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Previous studies have demonstrated some change in cortisol levels as a result of an art task (Lawson et al, 2012;Walsh et al, 2007). To the best of our knowledge, this is the first study to demonstrate reductions in cortisol levels in healthy adults as a result of art making in a format structured to be similar to an art therapy session.…”
Section: Discussionmentioning
confidence: 68%
“…Most studies, however, have tested art activities (Lawson et al, 2012;Mercer, Warson, & Zhao, 2010;Walsh et al, 2007) and used a specific art task or directive that may have influenced the outcomes. Thus it is unclear how structuring the session for free creative self-expression, viewed as similar as possible to an actual therapy situation and facilitated by an art therapist, would lower the stress response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Creative activity is understood as creative spending of time, making something, drawings, poems and so on. It has been found artistic activities can help in stress reduction of those suffering of chronic and serious diseases [11]. 3.…”
Section: Replacement Gratification -Techniques In-mentioning
confidence: 99%
“…Research into the effects of positive emotion suggest that it can improve subjective quality of life (Cho & Oh, 2011) and reduce treatment-related side effects and physiological markers of stress, including salivary cortisol levels in patients with cancer (Lawson et al, 2012). …”
Section: The Broaden and Build Theory Of Positive Emotions Is So Namementioning
confidence: 99%